Case report: Dissociative neurological symptom disorder with gait disturbance: taking after the father? - Geng, Wenqi; Jiang, Yinan; Wei, Jing (Frontiers in Psychiatry, 2024)
Dissociative neurological symptoms disorder (DNSD), or conversion disorder, frequently manifests with unexplained neurological symptoms, necessitating referral to psychiatry following preliminary diagnosis in neurology. We present a case of an adolescent female patient with gait disturbance as the predominant clinical presentation, and delve into the diagnosis and interdisciplinary intervention process. Given neuroimaging deviations detected and familial similar presentations, the organic etiology was confirmed. However, the aberrant gait remained unexplained ultimately prompting psychiatric consultation resulting in the diagnosis of DNSD. Interventions consisting of health education, suggestive therapy, and physiotherapy notably improved gait disturbance. However, at follow-up, the patient presented with a depressive episode. It was deduced that undiagnosed psychosocial factors, notably familial dynamics, likely contributed to this decline. Eventually, transformed relation patterns among family members as well as antidepressant treatment were instrumental in attaining symptom remission.